Determinants of long‐term survival in a population‐based cohort study of patients with head and neck cancer from Scotland. Issue 6 (8th January 2019) - Ingarfield, Kate; McMahon, Alex D.; Douglas, Catriona M.; Savage, Shirley‐Anne; Conway, David I.; MacKenzie, Kenneth
Abstract: Background: We investigated long‐term survival from head and neck cancer (HNC) using different survival approaches. Methods: Patients were followed‐up from the Scottish Audit of Head and Neck Cancer. Overall survival and disease‐specific survival were calculated using the Kaplan–Meier method. Net survival was calculated by the Pohar‐Perme method. Mutually adjusted Cox proportional hazards models were used to determine the predictors of survival. Results: A total of 1820 patients were included in the analyses. Overall survival at 12 years was 26.3% (24.3%, 28.3%). Disease‐specific survival at 12 years was 56.9% (54.3%, 59.4%). Net survival at 12 years was 41.4% (37.6%, 45.1%). Conclusion: Determinants associated with long‐term survival included age, stage, treatment modality, WHO performance status, alcohol consumption, smoking behavior, and anatomical site. We recommend that net survival is used for long‐term outcomes for HNC patients—it disentangles other causes of death, which are overestimated in overall survival and underestimated in disease‐specific survival.